The values of bureaucracy - Du Gay, Paul (Oxford University Press, 2005)
The end of bureaucracy has been anticipated many times throughout the history of management science as well as in modern social and political theory. This book sets out to show why bureaucracy persists and what values it embodies and upholds. Thus the book seeks to show how and why bureaucratic forms of organization have played, and continue to play, a vital and productive role in ordering our political, social, economic and cultural existence. This book also describes and analyzes the impact of contemporary programs of organizational reform in the public and private sectors on bureaucratic structures, and seeks to highlight some of the costs of attempts to debureaucratize organizational life in business, government, and the third sector. Overall the volume highlights the values of bureaucracy and at the same time indicates why distinctively bureaucratic forms of organization should continue to be valued.